Ilmenite-Apatite Mineralizations in the Lac-Saint-Jean and Labrieville Anorthositic Suites, Grenville Province, Quebec - A. -M. Cadieux (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
During the geological synthesis of the Réservoir Pipmuacan area (NTS 22E) by the Ministère des Ressources naturelles (Québec), several ilmenite-apatite occurrences, some well-known and some recently discovered, have been examined. These occurrences are hosted in the Lac-Saint-Jean and Labrieville AMCG anorthositic suites. The Lac-Saint-Jean Anorthositic Suite (1160-1140 Ma), composed of multiple intrusions covering an extensive surface area, is characterized by labradorite plagioclase. The Labrieville Anorthositic Suite (1010-1008 Ma) is characterized by andesine plagioclase. It was previously known as the Labrieville Anorthosite, which was composed of a small isolated pluton located east of the Lac-Saint-Jean Anorthositic Suite. However, new geochronological data and field observations indicate that the Labrieville Anorthositic Suite in fact includes several intrusive bodies, namely the La Hache Monzonite and the Mattawa Anorthosite. A series of major structures (Saint-Fulgence, Pipmuacan, and Chute-des-Passes deformation zones) and their conjugate faults played an important role in the emplacement of the Lac-Saint-Jean Anorthositic Suite. The Saint-Fulgence deformation zone appears to have been involved in the emplacement of the Labrieville Anorthositic Suite. Oxide mineralizations are abundant in both anorthositic suites. Ilmenite, magnetite (± titaniferous), and apatite assemblages are found mostly in the labradorite-type anorthosites, while hemo-ilmenite, magnetite and apatite assemblages are associated only with the andesine-type anorthosites. Field works has revealed ilmenite-apatite mineralizations in a variety of settings, with grades reaching 48% TiO2, 16.2% P2O5, and 71.7% Fe2O3 (tot). Numerous oxide-bearing gabbronorites, often accompanied by or located near massive apatite-oxide accumulations (nelsonites), were discovered. Among these oxide-rich zones, breccia zones with anorthosite enclaves in an oxide matrix (ilmenite-magnetiteapatite) have been observed. Locally, ilmenite-apatite mineralization occurs as cumulate concentrations in ultramafic rocks. Evidence has been observed for immiscible magmas, for magmas differentiated from a mangerite or jotunite parent, and even for late magmas differentiated from the anorthosite magma itself (apatite-bearing anorthosite). Finally, the northern part of the Lac-Saint-Jean Anorthositic Suite hosts sulfide and vanadium mineralizations associated with ilmenite-apatite enriched zones, with grades reaching 1.48% Cu, 1.22% Ni, 1.6% Cr2O5, 0.25% Co, and 0.52% V2O5.